An Analysis of Code-Mixing Used by Azka Corbuzier on Youtube Channel - Choi Sumaylan; M Zaim (English Language and Literature, 2023)
This research is aimed to analyze the types and the factors of code-mixing by Azka Corbuzier on two videos podcast YouTube channel. This research used a descriptive-qualitative method to analyze the data. The data of the research are from the utterances that contain words or phrases in code-mixing uttered by Azka Corbuzier as the speaker on the YouTube channel. The researcher found 125 data of code-mixing in Azka Corbuzier’s video podcast. The theory of Muysken (2000) is applied to identify the types of code-mixing in Azka Corbuzier’s podcast videos. Furthermore, the theory of Bhatia and Ritchie (2006) is used to determine the factor of code-mixing. The result of this research shows that the type of congruent lexicalization was the most common type of code-mixing found in the data. Meanwhile, the type of insertion was the least common type used by Azka Corbuzier. For the factor of code-mixing, participant roles and relationship factor was the most influential factor in code-mixing found in the data. Meanwhile, language attitude, dominance, and security were the least factors influencing Azka Corbuzier to use code-mixing. This research gives a contribution to sociolinguistics in terms of the code-mixing of a bilingual teenager.